Prevalence of metabolic syndrome and its components among men with and without clinical benign prostatic hyperplasia: a large, cross‐sectional, UK epidemiological study. (26th October 2015) - DiBello, Julia R.; Ioannou, Chris; Rees, Jonathan; Challacombe, Ben; Maskell, Joe; Choudhury, Nurul; Kastner, Christof; Kirby, Mike
Abstract : Objectives: To compare the prevalence of metabolic syndrome and the components of metabolic syndrome in men aged ≥50 years with and without clinical benign prostatic hyperplasia (BPH). Subjects and Methods: This was a cross‐sectional study using the UK Clinical Practice Research Datalink (CPRD). Men were selected from the CPRD who were aged ≥50 years and still registered as of 31 December 2011. Cohort 1 included men with clinical BPH, and cohort 2 men without clinical BPH who were matched 1:1 to those in cohort 1 by general practice, year of birth and previous years of available history (1–<2, 2–<3, 3–<4, ≥4 years of available history). The prevalence of metabolic syndrome and its components (for men alive and still registered in the CRPD as of 31 December 2011) was calculated using all available history (lifetime prevalence) and medical history from 2010 and 2011 (current prevalence). Crude odds ratios and 95% confidence intervals for the occurrence of metabolic syndrome and the occurrence of the components of metabolic syndrome were calculated by comparing men with and without BPH. Results: A total of 26.5% of men with clinical BPH had metabolic syndrome compared with 20.9% of matched controls without clinical BPH (absolute difference 5.6%; P < 0.001); men with clinical BPH were therefore significantly more likely to have metabolic syndrome than matched controls without clinical BPH. Significantly greater proportions of men with clinical BPH also had each component of metabolic syndrome compared with matched controls without clinical BPH. The presence of clinical BPH was associated with a 37% increased odds of having metabolic syndrome (for both lifetime prevalence and current prevalence) compared with matched controls without clinical BPH. Conclusions: There is a significant cross‐sectional association between clinical BPH and metabolic syndrome in the UK primary care population.